2020
DOI: 10.1021/acsaem.0c01336
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Properties of Aqueous Organic Redox Flow Battery Anolytes Using the Marcus–Hush Theory

Abstract: An electrochemical analysis strategy based on the Marcus–Hush approximation is presented to analyze the kinetic component of organic redox flow battery (RFB) electrolytes. The procedure was applied to aqueous solutions of methyl viologen (MV) and 2,2′-bipyridyl (diquat, DQ) derivatives as model redox-active electrolytes; although these systems are promising negolyte candidates in organic RFBs, their electrode kinetics continues to be unclear. For compound MV, the voltammetric analysis revealed an adsorption pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 57 publications
5
34
0
Order By: Relevance
“…Before testing an organic RFB, its redox active electrolyte solutions are typically characterized at low analyte concentrations close to 0.001 mol L –1 . , Under these conditions, the electrochemistry of compounds studied (Scheme ), also exemplified by the responses obtained from methyl viologen compound derivatives (Figure ), exhibits a first reversible one-electron transfer process in aqueous media to form radical cations A +• . Based on this experimental evidence, methyl viologen and diquat RFB electrolytes are assumed to operate in line with the mechanism described by eq , upon charging and discharging the device. , …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Before testing an organic RFB, its redox active electrolyte solutions are typically characterized at low analyte concentrations close to 0.001 mol L –1 . , Under these conditions, the electrochemistry of compounds studied (Scheme ), also exemplified by the responses obtained from methyl viologen compound derivatives (Figure ), exhibits a first reversible one-electron transfer process in aqueous media to form radical cations A +• . Based on this experimental evidence, methyl viologen and diquat RFB electrolytes are assumed to operate in line with the mechanism described by eq , upon charging and discharging the device. , …”
Section: Resultsmentioning
confidence: 99%
“…To rationalize how this widely proposed mechanism (eq ) affects the first electron transfer process (eq ) in compounds studied, a strategy based on performing cyclic voltammetry experiments at different initial analyte concentrations was addressed. The responses obtained from diquat solutions were taken as reference signals expected for simple one-electron transfer mechanisms since previous works have shown that electrogenerated diquat radical cations are stable in solution even at high concentrations of C * (0.03 and 0.10 mol L –1 ). , For this compound, reversible and diffusion-controlled one-electron voltammetric waves were detected in a wide range of analyte concentrations prepared (Figure A). The signals exhibited marginal changes in potential values and normalized peak current intensities versus C *, as described by the Randles–Cevcik equation in simple one electron transfer reactions; this result is disclosing the expected high stability of electrogenerated DQ +• species in solution.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations